Dynamic behavior of an active particle embedded in a smectic liquid crystal. - Mamani Arce, Yhony [UNESP] (UNESP, 2025)
Active matter systems, which continuously consume energy to generate directed motion, exhibit fascinating emergent phenomena. While their dynamics in isotropic fluids are well-understood, their behavior in complex, anisotropic environments remains a frontier of research. This dissertation investigates the transport properties of active Brownian particles (ABPs) in smectic-A (SmA) liquid crystal environments, specifically focusing on uniform configurations and those structured by Focal Conic Domains (FCDs). We employ numerical simulations to analyze the mean squared displacement (MSD), including its total, parallel, and perpendicular components, and the rotational mean squared displacement (RMSD) of ABPs. In a nearly flat SmA configuration, our results confirm characteristic ABP behavior, showing a transition from ballistic to enhanced diffusive motion, where the self-propulsion velocity dictates the effective diffusion coefficient. The alignment coupling between the ABP and the uniform director field significantly influences persistence, while the perpendicular MSD remains purely diffusive, consistent with a rigid, non-deformable medium. The introduction of mimetic FCDs leads to a more intricate dynamics. FCD singularities are identified as effective reorientation centers, where the rapidly changing local director field and the quadratic nature of the alignment interaction lead to stochastic reorientation of the ABPs. Consequently, the perpendicular MSD exhibits a transient superdiffusive regime at short times, attributed to the particle's persistent motion within a curving director landscape. Most notably, the parallel MSD displays a remarkable oscillatory behavior at intermediate to long times. The RMSD qualitatively reflects the interplay of rotational noise and alignment, with FCDs contributing to the overall random orientations. This work underscores the profound influence of complex, liquid crystalline architectures on active matter transport. Our findings provide fundamental insights into how spatial heterogeneity in soft matter systems can be leveraged to control and manipulate the dynamics of active agents, with implications for micro-robotics and active material design.

Sistemas de matéria ativa, que consomem energia continuamente para gerar movimento direcionado, exibem fenômenos emergentes fascinantes. Embora sua dinâmica em fluidos isotrópicos seja bem compreendida, seu comportamento em ambientes complexos e anisotrópicos permanece uma fronteira de pesquisa. Esta dissertação investiga as propriedades de transporte de partículas brownianas ativas (ABPs) em ambientes de cristal líquido esmético-A (SmA), com foco específico em configurações uniformes e aquelas estruturadas por Domínios Cônicos Focais (FCDs). Empregamos simulações numéricas para analisar o deslocamento quadrático médio (MSD), incluindo seus componentes total, paralelo e perpendicular, e o deslocamento quadrático médio rotacional (RMSD) de ABPs. Em uma configuração SmA ``quase plana'', nossos resultados confirmam o comportamento característico de ABPs, mostrando uma transição de movimento balístico para movimento difusivo mais intenso, onde a velocidade de autopropulsão determina o coeficiente de difusão efetivo. O acoplamento entre o alinhamento entre a ABP e o campo diretor uniforme influencia significativamente a persistência, enquanto o MSD perpendicular permanece puramente difusivo, consistente com um meio rígido e não deformável. A introdução de FCDs \emph{miméticos} leva a uma dinâmica mais complexa. As singularidades dos FCDs são identificadas como centros de reorientação eficazes, onde o campo diretor local fica sujeito a uma mudança rápida e a natureza quadrática da interação de alinhamento levam à reorientação estocástica das ABPs. Consequentemente, o MSD perpendicular exibe um regime superdifusivo transiente em tempos curtos, atribuído ao movimento persistente da partícula dentro de um perfil curvo dos diretores. De forma mais notável, o MSD paralelo exibe um comportamento oscilatório intrigante em regimes de tempos intermediários e longos. O RMSD reflete qualitativamente a interação entre ruído rotacional e o termo de alinhamento, com os FCDs contribuindo para as orientações aleatórias, em geral. Este trabalho destaca a influência profunda de estruturas líquido-cristalinas complexas no transporte de matéria ativa. Nossas descobertas fornecem insights fundamentais sobre como a heterogeneidade espacial em sistemas de matéria mole pode ser aproveitada para controlar e manipular a dinâmica de agentes ativos, com implicações para a microrrobótica e a projeção de materiais ativos.
Comportamento dinâmico de uma partícula ativa embutida em um cristal líquido esmético.
Keywords: Active Brownian Particles; Smectic-A; Focal Conic Domains; Mean Squared Displacement; Anisotropic Transport; Matéria condensada; Matéria condensada; Matéria condensada